Ethical implications of COVID-19 management-is freedom a desired aim, or a desired means to an end? - Andro Košec; Andro Košec; Filip Hergešić; Boris Zdilar; Lucija Svetina; Marko Ćurković; Marko Ćurković (Frontiers Media S.A., 2024)
Most developed societies managed, due to their prosperity and resource abundance, to structure relationships among free individuals in such a way to leave them fundamentally unstructured, according to the free market principle. As the pandemic illustrated well, this lack of structure when facing collective threats makes it impossible to collectively and proportionately assess and manage its implications and consequences. This may be particularly precarious when introducing comprehensive, monitoring and tracking, surveillance systems dependent on the vaccination status of the individual. If our previously shared aims were successfully and collectively enacted with the greatest of costs, is it permissible that the degree of personal freedom is a commodity, and everyone is a compulsory participant? The need to control one's COVID-19 status allows the individual to become legally free from excessive enactment of sovereignty of the state. Should these rights be regulated by the free market?